Quantum nonlinear optics - Hanamura, Eiichi. (Springer, 2007)
This graduate-level textbook gives an introductory overview of the fundamentals of quantum nonlinear optics. Based on the quantum theory of radiation, Quantum Nonlinear Optics incorporates the exciting developments in novel nonlinear responses of materials (plus laser oscillation and superradiance) developed over the past decade. It deals with the organization of radiation field, interaction between electronic system and radiation field, statistics of light, mutual manipulation of light and matter, laser oscillation, dynamics of light, nonlinear optical response, and nonlinear spectroscopy, as well as ultrashort and ultrastrong laser pulse. Also considered are Q-switching, mode locking and pulse compression. Experimental and theoretical aspects are intertwined throughout. Quantization of the radiation field -- Interaction between the electron and the radiation field -- Statistical properties of light -- Laser oscillation -- Dynamics of light -- Nonlinear optical responses I -- Nonlinear optical responses II.